Impact of the Construction of New Port Facilities on Primary Production of Plankton in the Neva Estuary (Baltic Sea) - Golubkov, Mikhail; Golubkov, Sergey (Frontiers in Marine Science, 2022)
A significant increase in the human population on marine coast and steady growth of maritime water transport causes the construction of port infrastructure and the creation of new lands, which affects the ecosystems of coastal waters. Despite the widespread occurrence of such large-scale engineering projects in coastal areas, their impact on various components of aquatic ecosystems, including phytoplankton, is still poorly understood. The aim of the study was to assess the effect of the construction of ports and the alluvium of new lands in the Neva Estuary in 2000s on the productivity of phytoplankton. Digging and dredging of bottom sediments results in one order of magnitude elevation of suspended particulate matter (SM), which mostly consisted of sand and clayed deposits and in significant decrease water transparency, as compared to the average long-term values. Concentrations of total phosphorus in the estuarine waters during the works significantly positively correlated with the concentrations of SM. However, the multiple increase in nutrients was less important for phytoplankton development than expected. Analysis of variance and stepwise multiple regression analyses showed that the main predictor of the primary production of plankton in the periods of construction was water transparency. Gross primary production decreased significantly. In contrast to short-term effects caused by wind-induced events, which often stimulated phytoplankton development, long-term construction works of new port facilities negatively influenced phytoplankton productivity. Apart from pristine conditions when the phosphorus concentration was the main factor limiting the primary production in the estuary, the main limiting factor during long-term engineering projects became water transparency. Taking into account plans for further development of ports in coastal areas around the world, the influence of the large-scale engineering projects on the conditions for the development of phytoplankton may provide a new aspect of long-term regulation of algal blooms and ecosystem functioning in the coastal and estuarine zone.